Influencia de la goma arabiga y antracita sobre la tensión de fibras textiles carbonizadas. - Farje Ocampo, Nadia Caroni (2011)
In this paper we study the influence of Arabic gum in tassel textile fibers, cotton, denim and linen to form a composite material. These materials were carbonized to obtain carbon fibers. The textile fiber tassel is study mainly for it presents a structure that collapses at temperatures below 275 ° C. It studies influence of Arabic gum as adhesive and anthracite as a reinforcing on composite material. The carbonized material quality is function of their tensile strength. The investigation variables are: ratio of arabic gum (adhesive) / water, anthracite as reinforcement and carbonization temperature. The results show that arabic gum prevents that fiber structure tassel collapse on carbonization. Anthracite under certain conditions increases the tensile strength. But temperature is a function of anthracite as reinforcement. The highest tensile strength is obtained for the initial composite material: tassel - Arabic gum -anthracite-tassel, carbonized at 275 ° C. The carbon fiber has strength of 44.2 N.